Pengaruh Reward Dan Pengembangan Karir Terhadap Retensi Karyawan Pada PT Cerita Rasa Nusantara Jakarta Selatan - Serly Sukawati; Fahmi Susanti (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to examine the effect of rewards and career development on employee retention at PT Cerita Rasa Nusantara, South Jakarta. The study uses a quantitative approach with a survey method by distributing questionnaires to 60 employees as respondents. The data analysis techniques employed are simple linear regression and multiple linear regression using SPSS version 28. The partial test results indicate that rewards (X1) have a positive and significant effect on employee retention (Y), with a significance value where t-calculated > t-table (5.650 > 2.002). Meanwhile, career development (X2) also has a positive and significant effect on employee retention, with a significance value where t-calculated > t-table (9.609 > 2.002). Simultaneously, rewards and career development have a significant effect on employee retention, as indicated by an F-calculated value of 46.129 > F-table of 3.16, with a significance level of 0.001 < 0.05. The coefficient of determination (R²) value of 0.618 indicates that rewards and career development contribute 61.8% to employee retention, while the remaining percentage is influenced by other factors outside this study